Towards a Sustainable Economy Paradoxes and Trends in Energy and Transportation (Sustainability and Innovation,, 2018)
This book provides an interdisciplinary account of how technological advances - mainly in the domains of energy and transportation - contribute to the transformation towards a more sustainable economic system. Drawing on methods from engineering, the management sciences and economics, which it combines in the framework of a systems sciences approach, the book presents qualitative and quantitative studies on government regulation, resources management and firms' strategy. Topics covered include the state-market dilemma of government CO2 emission targets, implications of the electrification of the economy, incentives and coercion in government transport policies, and innovations in the electric vehicle industry.